New Voices: A discussion of methods to measure the economic impact of art and cultural events - McInerney, Sian (Irish Journal of Arts Management and Cultural Policy, 2019)
This research paper interrogates the methods used by Grant Thornton to measure the economic impact of Limerick City of Culture and proposes alternate local/non-local expenditure segmentation as a more accurate method. The European Capital Cities of Culture and UK Capital of Culture initiatives have been viewed as successful cultural projects. In 2014 a similar initiative for Ireland, the National City of Culture, was launched with Limerick awarded the first title. Set broadly in the area of cultural economics, this paper discusses economic impact reporting techniques applied to the Limerick City of Culture in 2014. It concludes that a technique of segmentation of audience expenditures may contribute to a more accurate picture of economic impact of event attendees. It compares this process of segmentation to the methods employed by Grant Thornton in their Economic Impact Assessment of the Limerick City of Culture and concludes that economic techniques alone fail to capture the range of benefits that accrue from the existence of art and culture and should therefore be complemented by other tools, such as social impact assessments.